A xBP / g-C3N4 / BiOI ternary composite photocatalyst and its preparation method and application

By preparing xBP/g-C3N4/BiOI ternary composite photocatalyst, using black phosphorus to reduce charge transport barriers, the problem of low efficiency of existing photocatalysts in degrading difficult-to-degrade organic pollutants is solved, and efficient organic pollutant removal is achieved Effect.

CN118751266BActive Publication Date: 2025-02-07DALIAN NATIONALITIES UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410757409.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-13
Publication Date
2025-02-07
Estimated Expiration
2044-06-13

AI Technical Summary

Technical Problem

The existing photocatalysts have low efficiency in degrading difficult-to-degrade organic pollutants, high electron hole recombination rate, large band gap energy and limited catalytic activity, which limit their practical application in wastewater.

Method used

The xBP/g-C3N4/BiOI ternary composite photocatalyst was prepared by water bath heating and sonication method, and black phosphorus was used as electron buffering material to reduce the charge transport barrier between g-C3N4 and BiOI.

Benefits of technology

Under xenon lamp irradiation, xBP/g-C3N4/BiOI ternary composite photocatalyst has high efficiency in removing organic pollutants, especially the removal rate of tetracycline reaches 100% (120 minutes), and shows good stability and general Adaptability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004889895050000101
    Figure BDA0004889895050000101
  • Figure BDA0004889895050000102
    Figure BDA0004889895050000102
  • Figure BDA0004889895050000171
    Figure BDA0004889895050000171
Patent Text Reader

Abstract

The present invention provides a xBP / g‑C3N4 / BiOI ternary composite photocatalyst and a preparation method and application thereof, belonging to the technical field of photocatalytic materials. The method of the present invention comprises the following steps: using Bi(NO3)3·5H2O, KI and g‑C3N4 as raw materials, heating and reacting in a water bath to obtain g‑C3N4 / BiOI; dissolving black phosphorus and mixing it with the g‑C3N4 / BiOI in deionized water, and ultrasonically treating it to obtain the xBP / g‑C3N4 / BiOI ternary composite photocatalyst. The present invention uses black phosphorus as an electron buffer material and is prepared by a simple hydrothermal method. The ternary composite photocatalyst provided by the present invention has high removal efficiency for organic pollutants, good stability, is reusable, and has low biological toxicity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of photocatalytic materials, and in particular to a xBP / g-C3N4 / BiOI ternary composite photocatalyst and a preparation method and application thereof. Background Art

[0002] The rapid development of industrialization and urbanization has led to the deterioration of the ecological environment, mainly due to the inadequate management of various pollutants released during agricultural and industrial production processes. In recent years, various types of organic pollutants have been found in surface water, which are characterized by significant chemical stability and resistance to biodegradation. Moreover, these pollutants can accumulate in the human body through the food chain, posing a threat to human health. Various technologies have been used to eliminate organic pollutants from wastewater, including adsorption, biodegradation, electrochemical degradation, and photocatalytic degradation. However, traditional methods (such as physical adsorption and biological treatment) have some limitations, such as poor treatment effects or the generation of harmful byproducts during the treatment process. Photocatalytic technology is known for its environmentally friendly, sustainable and energy-saving characteristics, and has therefore attracted increasing attention for the degradation of organic pollutants. However, existing photocatalysts face many challenges, such as high electron-hole recombination rate, large band gap energy, and limited catalytic activity, which hinder their practical application. Therefore, there is an urgent need to find efficient photocatalysts that can degrade difficult-to-degrade organic pollutants in wastewater.

[0003] Graphene carbon nitride (g-C3N4) is a stable, non-toxic, cost-effective and easy-to-synthesize semiconductor photocatalyst. The band gap width of g-C3N4 is 2.7 eV, which enables it to function under visible light irradiation. However, the photocatalytic efficiency of g-C3N4 is still limited due to its limited absorption of visible light and the rapid recombination of photoinduced electrons and holes. Scientists have adopted a series of strategies to improve the photocatalytic performance of g-C3N4, including morphology regulation, element doping, noble metal deposition and heterostructure construction. g-C3N4 nanosheets have a large specific surface area and high charge separation efficiency. Therefore, constructing heterostructures based on g-C3N4 nanosheets is one of the most promising methods to improve its photocatalytic performance. Mao et al. constructed a heterojunction between MgO and g-C3N4, and the MgO / g-C3N4 photocatalyst exhibited a wider visible light response range, a lower electron-hole pair recombination rate, and a significantly higher hydrogen generation rate than pure g-C3N4. Therefore, it is crucial to select a photocatalyst that matches the energy level of g-C3N4.

[0004] In recent years, bismuth oxyhalides (BiOX, X = Cl, Br, I) have received widespread attention and can be applied to the degradation of organic pollutants, CO2 reduction, H2 generation, etc. Among them, bismuth oxyiodide (BiOI) has attracted much attention due to its excellent visible light absorption ability (band gap energy: 1.6-1.9 eV), and is often used as a photosensitizer for larger band gap semiconductors. In addition, the energy level of BiOI matches well with g-C3N4, and the relatively positive valence band position of BiOI can provide higher oxidation ability for photogenerated holes for the degradation of pollutants. Zhang et al. prepared the g-C3N4 / BiOI photocatalyst by hydrothermal synthesis, and the degradation rate constant for methylene blue (MB) was 0.0160min -1 , is pure g-C3N4(0.0028min -1 ) and BiOI(min -1 ) are 5.7 times and 3.9 times that of pure g-C3N4 and pure BiOI. Although the photocatalytic performance of binary composite materials is better than that of pure g-C3N4 and pure BiOI, further improving the photocatalytic efficiency of binary composite materials is crucial for practical applications. On this basis, Jiang et al. synthesized a BiOI / g-C3N4 / CeO2 ternary photocatalyst, which can degrade 90% of tetracycline (TC) within 120 minutes under visible light irradiation. Liao et al. synthesized a new g-C3N4 / BiOI / Ag2WO4 ternary photocatalyst at room temperature, and the degradation rate of Sudan III reached 89% within 90 minutes. In the design process of photocatalysts, it is crucial to consider the band gap of semiconductor materials, so this limits the material selection of ternary photocatalysts.

[0005] As one of the emerging two-dimensional layered materials, black phosphorus (BP) has developed rapidly in the fields of energy, biology and environmental applications due to its unique physical, chemical, optical and electrical properties. BP not only has high carrier mobility and anisotropy, but also has an adjustable band gap, ranging from 0.3eV to 2.0eV. These excellent properties enable BP to effectively match the band structure of other semiconductor materials.

[0006] Therefore, it is of great significance to prepare a ternary composite catalyst by combining BP with BiOX and C3N4 and explore its catalytic activity for the effective degradation of organic pollutants in wastewater. Summary of the invention

[0007] Based on the above content, the purpose of the present invention is to provide a xBP / g-C3N4 / BiOI ternary composite photocatalyst and its preparation method and application.

[0008] In order to achieve the above object, the present invention provides the following technical solution: a method for preparing a xBP / g-C3N4 / BiOI ternary composite photocatalyst, comprising the following steps:

[0009] Bi(NO3)3·5H2O, KI and g-C3N4 were used as raw materials and reacted by heating in a water bath to obtain g-C3N4 / BiOI;

[0010] The black phosphorus is dissolved and mixed with the g-C3N4 / BiOI in deionized water, and ultrasonic treatment is performed to obtain the xBP / g-C3N4 / BiOI ternary composite photocatalyst.

[0011] Preferably, the preparation method of g-C3N4 is: reacting melamine powder at high temperature to obtain g-C3N4.

[0012] Preferably, the molar ratio of the Bi(NO3)3·5H2O to the KI is 1:(0.9-1.1).

[0013] Preferably, the usage ratio of the Bi(NO3)3·5H2O to the g-C3N4 is (1.5-1.7) mmol: (180-220) mg.

[0014] Preferably, the water bath heating reaction is carried out at a temperature of 90-100° C. for 5-7 hours.

[0015] Preferably, the mass ratio of the black phosphorus to the g-C3N4 / BiOI is (2.5-25):500.

[0016] Preferably, the temperature of the ultrasonic treatment is 25-35°C and the time is 30-50 min.

[0017] Preferably, after the ultrasonic treatment is completed, the method further comprises the steps of filtering and drying the filtered sample.

[0018] The present invention also provides a xBP / g-C3N4 / BiOI ternary composite photocatalyst prepared by the preparation method described in the above technical solution.

[0019] The present invention also provides the use of the xBP / g-C3N4 / BiOI ternary composite photocatalyst in photocatalytic degradation of organic pollutants.

[0020] Beneficial technical effects:

[0021] The present invention uses black phosphorus (BP) as an electron buffer material and prepares a ternary composite photocatalyst of xBP / g-C3N4 / BiOI by a simple hydrothermal method. Under the irradiation of a xenon lamp, the ternary composite photocatalyst has a high removal efficiency for organic pollutants, especially for tetracycline (TC), with a removal rate of 100% (120 minutes).

[0022] The xBP / g-C3N4 / BiOI ternary composite photocatalyst provided by the present invention is universal for different water sources and has good stability and reusability. After continuous degradation tests, its lattice structure, chemical structure and surface morphology change slightly.

[0023] The plant toxicity evaluation experiment of the xBP / g-C3N4 / BiOI ternary composite photocatalyst provided by the present invention confirmed the non-toxicity of the TC and RhB degradation solutions. Compared with the untreated solution, the malondialdehyde and peroxidase indicators of the plants grown in the treated solution showed a downward trend. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 Schematic diagram of the preparation process of the present invention, wherein (a) is a schematic diagram of the preparation process of g-C3N4 / BiOI, and (b) is a schematic diagram of the preparation process of xBP / g-C3N4 / BiOI.

[0026] Figure 2 (a) and (b) are XRD spectra of different photocatalysts in Example 1, and (c) is the FT-IR spectrum of 2.5% BP / g-C3N4 / BiOI.

[0027] Figure 3 These are SEM images of the materials obtained in Example 1, where (a) is g-C3N4, (b) is BiOI, (c) is g-C3N4 / BiOI, and (d) is 2.5% BP / g-C3N4 / BiOI.

[0028] Figure 4 TEM images of 2.5% BP / g-C3N4 / BiOI prepared in Example 1 at different resolutions, where (a) is 100 nm and (b) is 50 nm.

[0029] Figure 5It is the XPS spectrum of 2.5% BP / g-C3N4 / BiOI in Example 1, wherein (a) is the full spectrum scan, (b) is C1s, (c) is N1s, (d) is O1s, (e) is I3d, (f) is Bi4f, and (g) is P2p; (h) is the UV-DRS of the prepared photocatalyst, (i) is the band gap energy of BP, g-C3N4 and BiOI; (j) is the PL spectrum, (k) is the transient photocurrent response, and (l) is the EISNyquist plot of BiOI, g-C3N4, g-C3N4 / BiOI and 2.5% BP / g-C3N4 / BiOI.

[0030] Figure 6 (a) and (b) are the degradation rates of TC by the prepared photocatalyst under simulated sunlight, (c) is the rate constant k for TC degradation by the prepared photocatalyst, and (d) is a comparison of the degradation performance of 2.5% BP / g-C3N4 / BiOI with g-C3N4, BiOI and BiOI / g-C3N4 related catalysts.

[0031] Figure 7 (a) shows the removal effect of 2.5% BP / g-C3N4 / BiOI on different organic pollutants under simulated sunlight; (b) shows the photocatalytic removal rate of TC and RhB in different water samples under 2.5% BP / g-C3N4 / BiOI conditions.

[0032] Figure 8 UV spectra of the degradation of organic dye solutions under different irradiation times, where (a) is RhB, (b) is CV, (c) is MB, and (d) is MG.

[0033] Fig. 9 (a) is the cyclic photocatalytic degradation experiment of TC under simulated sunlight on 2.5% BP / g-C3N4 / BiOI; (b) is the XRD spectrum of 2.5% BP / g-C3N4 / BiOI after four cycle tests, (c) is the FT-IR spectrum, and (d) is the SEM image.

[0034] Fig.10 Figure 2 shows the effect of different scavengers on the degradation of TC on 2.5% BP / g-C3N4 / BiOI (a) and the corresponding degradation rate (b). On 2.5% BP / g-C3N4 / BiOI, DMPO-·O2 - EPR spectra of DMPO-·OH in methanol (c) and in water (d).

[0035] Fig.11 3DEEMs fluorescence spectra of TC under different photocatalytic times, where (a) is 0 min, (b) is 30 min, (c) is 60 min, and (d) is 120 min.

[0036] Fig.12 The possible degradation pathway of TC on 2.5% BP / g-C3N4 / BiOI obtained in Example 1.

[0037] Fig.13 This is the possible photocatalytic mechanism of TC degradation on 2.5% BP / g-C3N4 / BiOI obtained in Example 1.

[0038] Fig.14 Results of evaluating various physiological indices of Chinese cabbage and rapeseed after seven days of treatment with deionized water, RhB solution, RhB degradation solution, TC solution, and TC degradation solution, including (a) length of Chinese cabbage germ; (b) length of rapeseed germ; (c) fresh weight of Chinese cabbage; (d) fresh weight of rapeseed; (e) MDA content; (f) POD activity. The box plots show the median represented by the solid line and the mean represented by the dashed line. DETAILED DESCRIPTION

[0039] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0040] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0041] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0042] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0043] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0044] The present invention provides a method for preparing a xBP / g-C3N4 / BiOI ternary composite photocatalyst, comprising the following steps:

[0045] Bi(NO3)3·5H2O, KI and g-C3N4 were used as raw materials and reacted by heating in a water bath to obtain g-C3N4 / BiOI;

[0046] The black phosphorus is dissolved and mixed with the g-C3N4 / BiOI in deionized water, and ultrasonic treatment is performed to obtain the xBP / g-C3N4 / BiOI ternary composite photocatalyst.

[0047] In some embodiments, the method for preparing the xBP / g-C3N4 / BiOI ternary composite photocatalyst specifically comprises the following steps: (the schematic diagram of the preparation process is shown in Figure 1 (shown)

[0048] S1. Dissolve Bi(NO3)3·5H2O in solvent I to obtain solution a, and dissolve KI in solvent II to obtain solution b;

[0049] S2. After mixing the solution a, solution b and g-C3N4, heating the mixture in a water bath to obtain g-C3N4 / BiOI;

[0050] S3. After dissolving black phosphorus in solvent III, mix it with the g-C3N4 / BiOI in deionized water and perform ultrasonic treatment to obtain the xBP / g-C3N4 / BiOI ternary composite photocatalyst (x is the ratio of BP to g-C3N4 / BiOI).

[0051] In some embodiments, the preparation method of g-C3N4 is: reacting melamine powder at high temperature to obtain g-C3N4; the reaction temperature is 500°C and the reaction time is 2h; after the reaction is completed, it also includes the step of cooling to room temperature and grinding using an agate mortar.

[0052] In some embodiments, the molar ratio of the Bi(NO3)3·5H2O to the KI is 1:(0.9-1.1), preferably 1:1.

[0053] In some embodiments, the usage ratio of the Bi(NO3)3·5H2O to the g-C3N4 is (1.5-1.7) mmol:(180-220) mg, preferably 1.6 mmol:200 mg.

[0054] In the present invention, when the ratio of Bi(NO3)3·5H2O to KI, Bi(NO3)3·5H2O to g-C3N4 is not within the above range, impurities and defects will be formed, reducing the stability and performance of the material. The mismatch of the raw material ratio may change the band gap energy of the photocatalyst, thereby affecting its absorption range of light. The correct ratio helps to optimize the separation of electrons and holes in the photocatalyst. If the raw material ratio is incorrect, the recombination rate of carriers may increase, thereby reducing the photocatalytic efficiency. The optimal raw material ratio helps to form more active sites, and deviations from the ratio may reduce the number of these sites, thereby reducing the catalytic activity.

[0055] In some embodiments, the water bath heating reaction is carried out at a temperature of 90-100° C., preferably 100° C., and the reaction time is 5-7 h, preferably 6 h.

[0056] In the present invention, too high a reaction temperature may cause the crystals to grow too fast, forming large particles, thereby reducing the specific surface area of ​​the photocatalyst. This will reduce the active sites and affect the catalytic performance. Too low a reaction temperature may result in a slower reaction rate and extend the preparation time. In addition, the surface of the photocatalyst may not be fully activated under low temperature conditions, thereby affecting its activity.

[0057] Too long a reaction time will cause the photocatalyst to grow excessively, forming large particles and reducing the specific surface area. In addition, a long reaction time may cause unnecessary side reactions and affect the purity of the product. Too short a reaction time may result in insufficient completion of the reaction, thereby affecting the structure and performance of the product. Therefore, the present invention preferably uses the above reaction temperature and time parameter ranges.

[0058] In some embodiments, after the water bath heating reaction is completed, the method further includes the steps of centrifugation to collect the precipitate, washing, and drying; the washing step is performed with deionized water and anhydrous ethanol; the drying temperature is 60° C., and the drying time is 6 hours.

[0059] In some embodiments, the mass ratio of the black phosphorus to the g-C3N4 / BiOI is (2.5-25):500.

[0060] In some embodiments, the mass ratio of the black phosphorus to the g-C3N4 / BiOI is 2.5:500, 5:500, 12.5:500, or 25:500.

[0061] The proportion of black phosphorus directly affects the catalytic performance of the obtained photocatalyst. As the content of black phosphorus increases, its catalytic performance gradually increases. However, when black phosphorus is excessive, its catalytic degradation performance is inhibited. In order to obtain better performance of photocatalytic degradation of pollutants, the mass ratio of black phosphorus to g-C3N4 / BiOI in the present invention is preferably within the above parameter range.

[0062] In some embodiments, the solvent I is ethylene glycol, the solvent II is distilled water, and the solvent III is N-methyl-2-pyrrolidone (NMP).

[0063] In some embodiments, the temperature of the ultrasonic treatment is 25-35° C., and the time is 30-50 min.

[0064] In some embodiments, after the ultrasonic treatment is completed, the method further includes filtering and drying the filtered sample; the drying temperature is 60° C. and the drying time is 6 hours.

[0065] The present invention also provides a xBP / g-C3N4 / BiOI ternary composite photocatalyst prepared by the preparation method described in the above technical solution.

[0066] The present invention also provides the use of the xBP / g-C3N4 / BiOI ternary composite photocatalyst in photocatalytic degradation of organic pollutants; the organic pollutants are tetracycline TC, rhodamine B (RhB), norfloxacin (NOR), malachite green (MG), crystal violet (CV) and methylene blue (MB); when the pollutant concentration is 10-50 mg / L, the dosage of the xBP / g-C3N4 / BiOI ternary composite photocatalyst in wastewater is 0.2 g / L-0.6 g / L.

[0067] Based on the high carrier mobility and adjustable band gap of black phosphorus (BP), the present invention uses it as an electron buffer material to reduce the charge transfer barrier between g-C3N4 and BiOI. The xBP / g-C3N4 / BiOI ternary composite photocatalyst was synthesized by a simple water bath method. The present invention evaluates the removal effect of the prepared photocatalyst on various organic pollutants (such as TC, rhodamine B (RhB), norfloxacin (NOR), malachite green (MG), crystal violet (CV) and methylene blue (MB)). In addition, the potential photocatalytic mechanism of the xBP / g-C3N4 / BiOI photocatalyst was elucidated through active species detection, reaction species capture experiments and in situ characterization. At the same time, TC degradation intermediates were identified by liquid chromatography-quadrupole mass spectrometry (LC-MS / MS, AB SCIEXAPI 3200), and possible degradation pathways were proposed. It is worth noting that plant toxicology experiments were carried out to analyze the ecotoxicity of TC and RhB degradation products. This study explored the introduction of charge-transfer buffer materials as a new approach to enhance photocatalytic performance, providing a feasible guideline for the effective degradation of organic pollutants in wastewater.

[0068] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0069] 1. The chemicals used in the examples are: melamine (C3H6N6, 99.5%) and nitro blue tetrazolium (NBT, 98.0%) provided by China Traditional Chinese Medicine Chemical Reagent Co., Ltd. Riboflavin (C 17 H 20 N4O6, 98.0%) and methionine (Met, 99.0%) were purchased from Shanghai McLean Biochemical Co., Ltd. Potassium dichromate (K2CrO7, 99.8%), potassium iodide (KI, 99.5%), bismuth nitrate (Bi(NO3)3·5H2O, 99.0%), ascorbic acid (VC, 99.7%), disodium hydrogen phosphate (NaH2PO4·H2O, 99.5%), ethylenediaminetetraacetic acid (EDTA, 99.0%) and isopropyl alcohol (IPA, 99.7%) were obtained from Tianjin Kemei Chemical Reagent Co., Ltd. Potassium bromide (KBr, 99.0%) and N-methyl-2-pyrrolidone (NMP, 99.9%) were purchased from Tianjin Damao Chemical Reagent Co., Ltd. Black phosphorus (BP, 99.9%) was purchased from Kunming Black Phosphorus Technology Service Company. All chemicals used in the present invention are analytically pure and do not require further purification. All reagents used in the present invention were not further purified.

[0070] 2. Characterization: The crystal structure of the photocatalyst was determined by X-ray diffractometer (XRD, Shimadzu XRD-6000). Fourier transform infrared spectrometer (FT-IR, Shimadzu IR Prestige-21) was used to characterize the photocatalyst at 400-4000 cm -1 The surface functional groups of the photocatalysts were analyzed within a range of 100 nm. The morphology and microstructure of the materials were observed using field emission scanning electron microscopy (FESEM, Hitachi S-4800) and transmission electron microscopy (TEM, JEOL-2100). The elemental composition and valence state of the elements were measured using an X-ray photoelectron spectrometer (XPS, Thermo ESCALAB 250XI). The light absorption properties of the synthesized samples were characterized by ultraviolet-visible diffuse reflectance spectroscopy (UV-vis DRS, Shimadzu UV-2600). The charge transfer properties of the photocatalysts were studied by fluorescence spectroscopy (PL, Shimadzu RF-6000). Electron paramagnetic resonance (EPR) spectra were obtained using a JEOL JES-FA200 EPR spectrometer, using 5,5-dimethyl-1-pyrrolidine-N-oxide (DMPO) as a capture agent.

[0071] 3. Photocatalytic experiment: 50mL TC solution (10mg / L) was added to a beaker, followed by 10mg of photocatalyst. The mixture was stirred for 10 minutes using a magnetic stirrer under dark conditions and then ultrasonicated for 20 minutes to ensure that the photocatalyst was evenly distributed in the TC solution and to establish adsorption-desorption equilibrium. The photocatalytic experiment was performed by irradiating the reaction solution with a 300W xenon lamp simulating sunlight. The reaction solution was taken out at given time intervals, filtered through a 0.22μm filter, and the absorbance at 357 / nm was measured using a UV-visible spectrophotometer. The degradation of pollutants during the photocatalytic process follows the pseudo-first-order kinetic model (Formula (1)):

[0072] ln(C t / C0)=-kt (1)

[0073] Where C0 is the initial pollutant concentration, C t is the pollutant concentration at time t, and k is the reaction rate constant. To evaluate the universal pollutant degradation ability of 2.5% BP / g-C3N4 / BiOI, degradation experiments of various organic dye pollutants and norfloxacin (NOR) were conducted. The experimental procedures and conditions were consistent with those of the TC experiment.

[0074] 4. Active species identification experiment: In order to reveal the contribution of active species in the degradation of pollutants by 2.5% BP / g-C3N4 / BiOI photocatalyst, VC, IPA, EDTA and K2Cr2O7 were used as superoxide anions (·O2 - ), hydroxyl radical (·OH), hole (h + ) and electron (e - ) were used for quenching experiments.

[0075] 5. Biological toxicity assessment: Cruciferous vegetable seeds (cabbage and rapeseed) that are sensitive to pollutants were selected as typical biological models to evaluate the ecotoxicity of the treatment solutions. Each treatment involved 60 seeds, and each culture dish contained three replicates, with 20 seeds in each culture dish. Before culturing, the seeds were placed in a 25mm×25mm weighing dish, treated with 1mL of 75% ethanol, and shaken for 30 seconds to remove impurities on the surface of the seeds. Then the ethanol was poured out and the seeds were rinsed three times with a large amount of deionized water, each rinse for 30 seconds. The cleaned seeds were transferred to a pre-prepared culture dish (90mm diameter), a qualitative filter paper was placed at the bottom of the culture dish, and then 5mL of culture solution was added. The control group was deionized water, and the treatment groups included RhB solution, RhB degradation solution, TC solution, and TC degradation solution. Before transferring to the culture dish, the treated seeds were rinsed with the treatment solution and wiped dry with a paper towel to eliminate the dilution effect of the residual deionized water on the culture solution and ensure the effective concentration of the culture solution. The seeds were cultured at room temperature in dark conditions. After 24 hours of incubation, the germination rate of the seeds was observed and all seeds were transferred to new dishes containing the same culture solution. The seeds were evenly arranged and further incubated for one week. On the seventh day, the taproot length, plant fresh weight and antioxidant index were measured.

[0076] 5.1 Biomass determination (fresh plant weight and radicle length)

[0077] After seven days of cultivation, photos of the germinated seeds were taken using a digital camera. Next, the radicle length of the germinated seeds was analyzed using ImageJ 1.50i software. After collecting the photos, the pakchoi and rapeseed seedlings were rinsed three times with deionized water. After wiping the surface moisture with filter paper, the weight of the plants was measured using a balance.

[0078] 5.2 Antioxidant enzyme activity

[0079] The peroxidase (POD) enzyme activity was determined using the Guaiacol method. Take 3 mL of the reaction mixture and 30 μL of the sample, and phosphate buffered saline (PBS) is used as a control for zero point adjustment. Subsequently, the absorbance is measured at 470 nm (OD470). The enzyme activity is calculated as follows:

[0080]

[0081] Where ΔA 470 is the change in absorbance within 40 seconds, and t is 40 seconds.

[0082] 5.3 Antioxidant enzyme activity

[0083] The MDA content was determined using the thiobarbituric acid (TBA) reaction method. 0.2 g of fresh leaves were homogenized in 1.6 mL of 10% trichloroacetic acid (TCA) and centrifuged at 10,000 rpm for 20 min. The supernatant (0.75 mL) obtained was mixed with 0.75 mL of 0.67% thiobarbituric acid, heated at 95 ° C for 30 min, and then rapidly cooled to freezing point. After centrifugation at 10,000 rpm for 10 min, the absorbance was measured at 532 nm using a full wavelength microplate reader (FWMR, TECANSPARK10M), and nonspecific turbidity was corrected by subtracting the absorbance at 600 nm and 450 nm. The concentration of MDA in the extract was calculated using the following formula:

[0084]

[0085] Where V is the volume of the supernatant (1.6 mL), OD 532 OD 600 and OD 450 are the absorbance values ​​at 532 nm, 600 nm and 450 nm respectively, and FW is the weight of the sample (0.2 g).

[0086] In the following example, g-C3N4 was prepared by heating melamine powder (200 mg) at 500°C for 2 hours, cooling to room temperature, and then grinding with an agate mortar to obtain powdered g-C3N4.

[0087] Preparation of BiOI (BiOI was prepared by chemical bath method): 1.6 mmol Bi(NO3)3·5H2O and 1.6 mmol KI were dissolved in 76 ml ethylene glycol and 4 ml distilled water, respectively, and mixed. The mixed solution was then heated in a 100°C water bath for 6 h. The obtained BiOI was collected by centrifugation, washed with deionized water and anhydrous ethanol several times, and dried at 60°C for 6 h.

[0088] Example 1

[0089] Preparation of xBP / g-C3N4 / BiOI:

[0090] Step 1. Dissolve 1.6 mmol of Bi(NO3)3·5H2O in 76 mL of ethylene glycol to obtain solution a, and dissolve 1.6 mmol of KI in 4 mL of distilled water to obtain solution b.

[0091] Step 2. Add 200 mg g-C3N4 and solution a to solution b and stir, then heat in a water bath at 100°C for 6 hours, collect the precipitate by centrifugation, wash it with deionized water and anhydrous ethanol several times, and dry it at 60°C for 6 hours to obtain g-C3N4 / BiOI.

[0092] Step 3. BP (2.5 mg, 5 mg, 12.5 mg and 25 mg) was dissolved in N-methyl-2-pyrrolidone, and then mixed with 500 mg of g-C3N4 / BiOI obtained in step 2 in 100 mL of deionized water, ultrasonically treated at 30°C for 40 minutes, filtered, and the filtered sample was dried at 60°C for 6 hours to obtain a composite photocatalyst, labeled as xBP / g-C3N4 / BiOI. (x is the ratio of BP to g-C3N4 / BiOI, which are 0.5%, 1%, 2.5%, and 5%, respectively).

[0093] The lattice structure, chemical structure, surface morphology and elemental composition of the prepared photocatalyst were observed by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray photoelectron spectroscopy (XPS). XRD patterns were collected to study the lattice structure. Figure 2 As shown in Figure 2, the diffraction peak of g-C3N4 is located at 27.5°, which can be attributed to the (002) crystal plane of graphene, consistent with the results reported previously. The diffraction peaks of BiOI were observed to be located at 31.7°, 39.4°, 45.4°, 51.3° and 65.5°, corresponding to the (110), (004), (200), (114) and (106) crystal planes of BiOI, respectively (JCPDS No. 10-0445). The XRD pattern of xBP / g-C3N4 / BiOI clearly shows the diffraction peaks of g-C3N4, BiOI and BP, and there are no other diffraction peaks, indicating the successful synthesis of the ternary composite material. In addition, the intensity of the BP peak increases significantly with the increase of BP content.

[0094] The chemical structure of the composites was evaluated by FT-IR. 250-1629cm -1 and 809cm -1 The characteristic absorption peaks at 3228-3577 cm-1 correspond to the CN heterocycle and S-triazine unit 40 of g-C3N4 and 2.5% BP / g-C3N4 / BiOI, respectively, indicating that the chemical structure of g-C3N4 remains intact after modification with BP and BiOI. In addition, due to the overlap of NH and OH absorption peaks, -1 The absorption peak at 768 cm in the FT-IR spectra of BiOI and 2.5% BP / g-C3N4 / BiOI -1 The absorption peak at 2354 cm is attributed to the symmetric stretching vibration of the Bi-O bond. -1 The characteristic peak at is due to the formation of strong PO-Bi bonds. The results of FT-IR confirm the successful preparation of BP, BiOI and g-C3N4 composites.

[0095] The microstructure and surface morphology of the prepared photocatalyst were analyzed by SEM ( Figure 3 ) and TEM( Figure 4 ) were studied. Figure 3 As shown in (a), the SEM image of g-C3N4 shows a typical stacked nanosheet structure. Figure 3 (b) shows a 3D nanoflower structure composed of BiOI nanosheets of different thicknesses. Figure 3 In (c), the distribution of BiOI on the g-C3N4 surface can be observed. Figure 3 (d) shows the SEM image of 2.5% BP / g-C3N4 / BiOI, revealing the close connection between BP and BiOI nanoparticles and g-C3N4. TEM image ( Figure 4 ) further confirmed the presence of g-C3N4 and BiOI on the BP surface. The heterostructure formed by g-C3N4, BiOI and BP facilitates charge transfer and may improve the photocatalytic degradation efficiency of the composite.

[0096] XPS spectrum of 2.5%BP / g-C3N4 / BiOI photocatalyst ( Figure 5 ) confirmed the existence of five main elements: N, O, P, I and Bi. Figure 5 (b) shows a high-resolution scan of the C1s peak, where the peaks at 284.6 eV, 286.3 eV, and 288.6 eV correspond to CC, C-(N)3, and NC=N, respectively. Figure 5 As shown in (c), the high-resolution N1s spectrum of 2.5%BP / g-C3N4 / BiOI can be divided into three sub-peaks: CN=C at 398.5eV, N-(C)3 at 399.5eV, and π excitation at 399.5eV. O 1s spectrum ( Figure 5 (d) shows a distinct peak at 532.8 eV, attributed to surface OH, and 533.5 eV, corresponding to adsorbed H2O. The two peaks at 529.4 eV and 531.8 eV are indicative of Bi-O bonds. In the high-resolution spectrum of Bi 4f ( Figure 5 In (f), two peaks appeared at 164.8 eV and 159.4 eV, corresponding to Bi 4f5 / 2 and Bi 4f7 / 2, respectively. Figure 5 (e) shows two obvious peaks at 630.4eV and 618.8eV, corresponding to I 3d3 / 2 and I 3d5 / 2, respectively. Figure 5 In (g), the two peaks decomposed are located at 132.8eV and 129.3eV, corresponding to the electron orbitals P 2p 3 / 2 and P 2p1 / 2 The above results further confirmed the coexistence of BiOI, g-C3N4 and BP in 2.5%BP / g-C3N4 / BiOI.

[0097] Optical and optoelectronic properties:

[0098] The optical properties of the prepared photocatalysts were characterized by diffuse reflectance spectroscopy (DRS). Figure 5 As shown in (h), BP shows a wide absorption range from the ultraviolet to the near-infrared region. The maximum absorption edges of g-C3N4 and BiOI are approximately 465nm and 567nm, respectively. g-C3N4 / BiOI and 2.5% BP / g-C3N4 / BiOI show a significant red shift in light absorption, indicating good light absorption performance. After composite materials, the spectral response range of g-C3N4 / BiOI and 2.5% BP / g-C3N4 / BiOI is expanded, which contributes to visible light absorption and is beneficial to the photocatalytic reaction. According to the UV-visible diffuse reflectance absorption spectrum, the band gap width of BP, g-C3N4 and BiOI materials was calculated based on formula (4):

[0099] (αhv) 1 / n =C(hv-Eg) (4)

[0100] Where α, h, ν, C and Eg represent the absorption coefficient, Planck constant, optical frequency, constant and band gap width of the material, respectively. BP is a direct band gap semiconductor, while BiOI and g-C3N4 are indirect band gap semiconductors. Therefore, the n value of BP is 1 / 2, while the n values ​​of g-C3N4 and BiOI are 2. According to the diffuse reflectance absorption spectrum, the band gaps of BP, g-C3N4 and BiOI are approximately 1.50eV, 2.68eV and 1.90eV, respectively ( Figure 5 (i)).

[0101] The recombination performance of photogenerated electron-hole pairs is one of the key parameters for evaluating photocatalytic performance and is crucial for subsequent photocatalytic applications. In order to study the effect of BP introduction on the photoelectrochemical performance of photocatalysts, electrochemical measurements such as photoluminescence (PL) spectroscopy, transient photocurrent (TPC) and electrochemical impedance spectroscopy (EIS) were performed on the prepared photocatalysts. The photogenerated carriers of the prepared photocatalysts were investigated by PL spectroscopy analysis. Figure 5 As shown in (j), the PL intensity of g-C3N4 / BiOI is significantly lower than that of BiOI and g-C3N4, which is attributed to the formation of heterojunction between BiOI and g-C3N4. Compared with the other three photocatalysts, 2.5% BP / g-C3N4 / BiOI exhibits lower luminescence intensity, indicating that the addition of BP effectively suppresses the recombination of electrons and holes. The separation characteristics of photogenerated carriers were explored by measuring the transient photocurrent density of 5 intermittent cycles ( Figure 5 (k)). The results show that under irradiation conditions, 2.5% BP / g-C3N4 / BiOI exhibits the highest photocurrent density, indicating its excellent ability to generate photogenerated electron-hole pairs. The charge transport ability of the photocatalyst was analyzed by the EIS Nyquist plot. A smaller arc radius indicates a lower charge transfer impedance and a stronger charge transport ability. Figure 5 As shown in (l), 2.5% BP / g-C3N4 / BiOI exhibits the smallest arc radius among the prepared photocatalysts, indicating its higher charge transport capacity. The results show that the introduction of BP into the ternary composite photocatalyst effectively inhibits the recombination of photogenerated carriers, thereby improving the photocatalytic activity.

[0102] Effect verification:

[0103] 1. Photocatalytic degradation performance:

[0104] The photocatalytic degradation performance was studied using TC as the pollutant under simulated sunlight irradiation. Figure 6 As shown in (a) and (b), when no photocatalyst was added, the TC concentration had almost no significant change, confirming that light alone hardly degraded TC. The binary g-C3N4 / BiOI photocatalyst achieved a 78% degradation rate of TC within 120 minutes under simulated sunlight. When the BP content increased from 0.5% to 2.5%, the photocatalytic performance of TC degradation gradually enhanced. 2.5% BP / g-C3N4 / BiOI achieved a 100% degradation rate of TC within 120 minutes through the photocatalytic process. However, when the BP content reached 5%, the amount of TC removed was lower than that of 2.5% BP / g-C3N4 / BiOI, indicating that excess BP has an inhibitory effect on TC degradation. As Figure 6 As shown in (c), the rate constant (k, 0.032min) of 2.5%BP / g-C3N4 / BiOI -1 ) is higher than other photocatalysts. Compared with the reported photocatalysts related to g-C3N4, BiOI and BiOI / g-C3N4, 2.5% BP / g-C3N4 / BiOI exhibited efficient photocatalytic performance for pollutant degradation ( Figure 6 (d) and Table S1).

[0105] In order to study the universality of the photocatalytic process of 2.5%BP / g-C3N4 / BiOI, several organic pollutants (such as TC, NOR and organic dye pollutants RhB, MG, CV and MB) were degraded. Figure 7 As shown in (a), MG was completely degraded within 30 min, and the removal efficiencies of CV and MB reached approximately 100% and 93% within 60 min and 90 min, respectively. Figure 8The UV-visible absorption spectra of different organic dyes during the photocatalytic degradation process are shown. Over time, the intensity of the characteristic absorption peaks of various organic dyes gradually decreases. The color also gradually fades and eventually becomes colorless. On 2.5% BP / g-C3N4 / BiOI, the removal rate of NOR can reach 88% within 150 minutes, which is lower than TC. The results show that 2.5% BP / g-C3N4 / BiOI has good universality for the photocatalytic degradation of organic pollutants.

[0106] To evaluate the adaptability of the photocatalytic process to 2.5% BP / g-C3N4 / BiOI, we conducted TC and RhB degradation experiments in different real water samples, such as Jinzhou District tap water (39.046°N, 121.769°E), Paotaishan Park lake water (39.053°N, 121.763°E), and Dalian seawater (39.030°N, 121.76°E). Figure 7 As shown in (b), the degradation performance of 2.5% BP / g-C3N4 / BiOI for TC and RhB in the three real water samples is slightly lower than that in deionized water, which is due to the presence of complex inorganic anions and natural organic matter in these three water samples, which quench the active species. In tap water (85.26% and 88.46%), 2.5% BP / g-C3N4 / BiOI exhibited higher RhB and TC degradation efficiency than in lake water (75.14% and 81.63%) and seawater (72.31% and 70.32%), which is attributed to the less inorganic anions and natural organic matter in tap water. The results emphasize the influence of inorganic anions and natural organic matter on the photocatalytic degradation performance.

[0107] The recyclability of 2.5%BP / g-C3N4 / BiOI was investigated by continuous TC removal experiments. Fig. 9 In (a), the removal efficiency of TC exceeded 93% in the 120-min photocatalytic process, while the removal efficiency of RhB exceeded 98% in 90 min. We also examined the lattice structure, chemical structure, and morphology of 2.5% BP / g-C3N4 / BiOI before and after the continuous degradation experiment. Characterization results (XRD patterns ( Fig. 9 (b)), FT-IR spectrum ( Fig. 9 (c)) and SEM images ( Fig. 9 (d)) shows that the lattice structure, chemical structure and surface morphology of 2.5%BP / g-C3N4 / BiOI changed slightly after continuous degradation test. The above results verify the stability of 2.5%BP / g-C3N4 / BiOI for photocatalytic process.

[0108] 2. The degradation mechanism of pollutants by 2.5% BP / g-C3N4 / BiOI during photocatalysis:

[0109] To reveal the reactant contribution of 2.5%BP / g-C3N4 / BiOI to pollutant removal during the photocatalytic process, VC, IPA, EDTA, and K2Cr2O7 were used as specific scavengers to remove ·O2 - , OH, h + and e - Perform quenching experiments. Fig.10 As shown in (a) and (b), the removal rate of TC decreased with the addition of scavengers. Specifically, the photocatalytic activity of 2.5% BP / g-C3N4 / BiOI for TC degradation decreased significantly after the addition of VC, indicating that·O2 - is the main oxidizing species. In general, the degradation of TC is attributed to the comprehensive reactions of various reactive species.

[0110] In order to confirm the generation of reaction species during the photocatalytic process, electron paramagnetic resonance (EPR) spectroscopy was used to detect ·O2 using 5,5-dimethyl-1-pyrrolidine nitroxide (DMPO) as a capture agent. - and OH. Fig.10 As shown in (c) and (d), there is no obvious EPR response under dark conditions. Under xenon lamp irradiation, after adding 2.5% BP / g-C3N4 / BiOI, DMPO-·O2 - and DMPO-·OH adducts increased with time. The results verified that the photocatalytic process - and ·OH production.

[0111] In order to study the degradation mechanism of pollutants by 2.5% BP / g-C3N4 / BiOI during photocatalysis, three-dimensional excitation-emission matrix fluorescence spectroscopy (3DEEMs) was used to detect the changes in fluorescence during the photocatalytic process. Fig.11 (a)-(d) show the 3DEEMs fluorescence spectra of residual TC solution at different times. Fig.11 As shown in (a), there is no obvious fluorescence signal in the original TC solution, which is due to the presence of multiple electron-absorbing groups in the TC molecule. After 30 minutes of photocatalytic reaction, two fluorescence signals caused by humic acid appeared, located at Ex / Em=225-275 / 325-425nm and Ex / Em=275-350 / 325-575nm ( Fig.11 (b)). As the reaction time increases, the intensity of these two fluorescence signals gradually increases ( Fig.11 (c)), indicating that TC further degraded. At 120 minutes ( Fig.11In (d), both fluorescence signals are very weak, indicating that most of TC and its intermediates have been mineralized into CO2 and H2O.

[0112] To gain a deeper understanding of the degradation mechanism of TC, we analyzed the possible degradation pathways. The intermediates produced during the photocatalytic degradation of TC (Table S1) were analyzed by LC-MS / MS. Based on the detected intermediates, two possible degradation pathways for the photocatalytic degradation of TC on 2.5% BP / g-C3N4 / BiOI were proposed ( Fig.12 ). In general, the benzene ring, C=C double bond, and low-energy CN bond in TC are susceptible to attack by free radicals. In pathway 1, the N-(CH3)2 group at TCC-4 is demethylated to form P1, and demethylation and dehydrogenation occur simultaneously to form P2. Subsequently, the -CO group in P2 is cleaved to form compound P3. Finally, P3 is deaminated to form P4. Pathway 2 involves the attack of ROS on the amide group at TCC-1. The attack of ROS leads to the deacylation of the TC structure to form the intermediate P5. By cleavage and dehydration of the N,N-dimethyl group of P5, byproducts P6 and P7 are obtained. The loss of the aldehyde group and the cleavage of the carbon-carbon double bond in P7 lead to the formation of P8 and P9. The cleavage of the double bond in P7 can generate P10. Subsequently, both pathways produce degradation products with lower molecular weight. Further degradation leads to oxidation of the carboxamide group and the double bond, producing tertiary degradation products with lower molecular weight. Ultimately, the products decompose into CO2, H2O, and small organic acids.

[0113] By calculating the relative valence band position (EVB) and conduction band position (ECB) of BP, g-C3N4 and BiOI, the transport paths of photoinduced electrons and holes were analyzed, which is beneficial to study the photocatalytic mechanism of pollutant removal on 2.5% BP / g-C3N4 / BiOI. The theoretical band position can be derived from the empirical formula based on M.Maliken's electronegativity theory (Formula (4)-(5)):

[0114] E VB =X-Ee+0.5Eg(4)

[0115] E CB =E VB -Eg(5)

[0116] Where E CB , E VB , Ee, X and Eg represent the potential of the conduction band (CB), the potential of the valence band (VB), and the energy of free electrons on the hydrogen scale (about 4.5 eV). The E of BP, g-C3N4 and BiOI are calculated. VB The values ​​are 1.87eV, 1.56eV and 2.66eV respectively. The E CBThe values ​​are 0.37eV, -1.12eV and 0.76eV, respectively. By calculation, the migration of electrons in g-C3N4 to BiOI needs to overcome a barrier height of 1.88eV in the composite material of g-C3N4 and BiOI. This barrier height is relatively large, which hinders the migration of electrons. In organic photovoltaic devices, a buffer layer is usually introduced between the electrode and the active layer to enhance the migration of charge carriers from the active layer to the electrode to reduce the barrier height. The conduction band edge of BP is about 0.37eV, which makes it located between the conduction band edges of g-C3N4 and BiOI. The introduction of BP forms two contact interfaces of BP / g-C3N4 and BP / BiOI. The calculated barrier heights of the BP / g-C3N4 and BP / BiOI interfaces are 1.49eV and 0.39eV, respectively. Therefore, the introduction of BP on g-C3N4 / BiOI can reduce the barrier height to enhance the migration of charge carriers, thereby achieving efficient photocatalytic performance for pollutant removal.

[0117] Based on the above results, the energy band structure and potential photocatalytic degradation mechanism of 2.5%BP / g-C3N4 / BiOI were proposed and explained, such as Fig.13 As shown. First, g-C3N4 and BiOI absorb photons with energy equal to or greater than their respective band gaps under xenon lamp irradiation. The electrons in the valence bands of g-C3N4 and BiOI are excited to their respective conduction bands, generating electron-hole pairs. Then, the photogenerated electrons can transfer from g-C3N4 to BiOI through a new pathway. The electrons transfer from g-C3N4 to BP through a low barrier (1.49 eV), and then transfer to BiOI through another low barrier (0.39 eV). The photogenerated electrons accumulated in the conduction band of BiOI can react with O2 to generate O2 - , which may be due to the activation of O2 to generate O2 - The reduction potential of excess ·O2- and H + and e - The reaction generates H2O2, followed by the formation of ·OH. Finally, the holes can be directly transferred from the valence band of BiOI to the valence band of g-C3N4. - The redox potential of OH (+1.99 eV) is higher than that of holes in the valence band (+1.56 eV), so it cannot pass through OH. - Directly generate ·OH. The remaining holes in the valence band of g-C3N4 show strong oxidizing properties for pollutant degradation. The relevant reaction equations in the photocatalytic process are summarized as follows (Formulas (6)-(10)):

[0118] 2.5%BP / g-C3N4 / BiOI+hv→g-C3N4(h + +e - )+BiOI(h + +e -)→g-C3N4(h + )+BiOI(e - )(6)e - +O2 → ·O2 - (7)

[0119] O2 - +2H + +e - →H2O2(8)

[0120] H2O2+e - → OH+OH - (9)

[0121] h + +e - +·O2-+·OH+TC→degradationproducts(10)

[0122] 3. Toxicity Assessment

[0123] By evaluating various physiological parameters of cabbage and rapeseed seeds under different solutions, the effects of deionized water, RhB solution, degraded RhB solution, TC solution and degraded TC solution on plant growth were evaluated. Fig.14 (a)-(d) show the germination images and fresh weight box plots of cabbage and rapeseed seeds after seven days of treatment with different solutions. TC and RhB solutions have a significant inhibitory effect on seed growth. After seven days of germination, the root length and fresh weight of plants cultured in organic pollutant solutions were significantly lower than those in deionized water. However, the root length and fresh weight of plant seeds cultured in organic pollutant degradation solutions were slightly higher than those of blank samples. This is because the organic pollutant degradation solution contains nitrogen, carbon and trace elements that are beneficial to plant growth and development. The damage to plants before and after treatment with organic pollutant aqueous solutions was further investigated and evaluated by measuring two oxidative stress indicators, malondialdehyde (MDA) and peroxidase (POD). MDA is a product generated by lipid peroxidation under stress conditions and has certain cytotoxicity. It is often used as a key indicator to measure the degree of oxidative damage; higher MDA levels indicate more severe cell damage. POD can decompose reactive oxidative substances (ROS) in plants, thereby protecting plant cells from oxidative damage. As Fig.14 As shown in (e) and (f), the MDA content and POD activity of the plant seeds cultured in the organic pollutant degradation solution are lower than those of the plant seeds cultured in the organic pollutant aqueous solution. The above results show that the ecotoxicity of TC and RhB aqueous solutions treated with 2.5% BP / g-C3N4 / BiOI is significantly reduced.

[0124] Table S1 LC-MS / MS detection of TC degradation intermediates.

[0125]

[0126]

[0127]

[0128] In summary, the present invention prepared xBP / g-C3N4 / BiOI photocatalyst by a simple water bath method. The introduction of BP as an electron buffer material reduced the charge transfer barrier between g-C3N4 and BiOI, allowing the effective separation of photogenerated electrons. Under simulated sunlight irradiation, 2.5% BP / g-C3N4 / BiOI showed excellent pollutant removal performance. EPR tests and free radical capture experiments showed that the introduction of BP on g-C3N4 / BiOI produced abundant ·O2 - and ·OH, which play a key role in the degradation of pollutants. The possible degradation pathways of TC were speculated using LC-MS / MS and 3DEEMs techniques. Toxicity experiments on plants (cabbage and rapeseed) showed that solutions containing TC and RhB degradation products were not toxic to plants. Further research on the damage to plants before and after treatment with organic pollutant solutions revealed a downward trend in MDA and POD in plant tissues by measuring these two indicators as indicators of oxidative stress. This invention provides new insights into the design of advanced photocatalysts for pollutant degradation in photocatalytic processes.

[0129] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Application of a xBP / g-C3N4 / BiOI ternary composite photocatalyst in photocatalytic degradation of organic pollutants, characterized in that: The preparation method of the xBP / g-C3N4 / BiOI ternary composite photocatalyst comprises the following steps: Bi(NO3)3·5H2O, KI and g-C3N4 were used as raw materials and reacted by heating in a water bath to obtain g-C3N4 / BiOI; Dissolving black phosphorus and mixing it with the g-C3N4 / BiOI in deionized water, and ultrasonically treating the mixture to obtain the xBP / g-C3N4 / BiOI ternary composite photocatalyst; The molar ratio of Bi(NO3)3·5H2O to KI is 1:(0.9-1.1); The usage ratio of the Bi(NO3)3·5H2O to the g-C3N4 is (1.5-1.7) mmol: (180-220) mg; The water bath heating reaction temperature is 90-100°C and the time is 5-7h; The mass ratio of the black phosphorus to the g-C3N4 / BiOI is (2.5-25):500; The organic pollutant is tetracycline, rhodamine B, norfloxacin, malachite green, crystal violet or methylene blue.

2. The use of the xBP / g-C3N4 / BiOI ternary composite photocatalyst in photocatalytic degradation of organic pollutants according to claim 1, characterized in that: The preparation method of g-C3N4 is: reacting melamine powder at high temperature to obtain g-C3N4.

3. The use of the xBP / g-C3N4 / BiOI ternary composite photocatalyst in photocatalytic degradation of organic pollutants according to claim 1, characterized in that: The temperature of the ultrasonic treatment is 25-35°C and the time is 30-50 minutes.

4. The use of the xBP / g-C3N4 / BiOI ternary composite photocatalyst in photocatalytic degradation of organic pollutants according to claim 1, characterized in that: After the ultrasonic treatment is completed, the steps of filtering and drying the filtered sample are also included.

Citation Information

Patent Citations

  • Composite photocatalyst, and preparation method and application of composite photocatalyst

    CN108654671A